Inherent and acquired resistance to paclitaxel in hepatocellular carcinoma: molecular events involved. - Avtar Singh Meena; Aanchal Sharma; Ratna Kumari; Naoshad Mohammad; Shivendra Vikram Singh; Manoj Kumar Bhat (PLoS ONE, 2013)
Hepatocellular carcinoma (HCC) is a primary malignancy of the liver and is a major cause of cancer related deaths worldwide. Only 10 to 20% of HCC can be surgically excised. Therefore, chemotherapeutic intervention and treatment is essential for achieving favorable prognosis. However, therapeutic outcome of chemotherapy is generally poor owing to inherent resistance of cancer cells to the treatment or due to development of acquired resistance. To differentiate and delineate the molecular events, we developed drug resistant Hep3B cells (DRC) by treating cells with the increasing concentration of paclitaxel. We also developed a unique single cell clone of Hep3B cells (SCC) by selecting single cell colonies and screening them for resistant phenotype. Interestingly, both DRC and SCC were resistant to paclitaxel in comparison to parental Hep3B cells. We analyzed the contributory factors that may be involved in the development of resistance. As expected, level of P-glycoprotein (P-gp) was elevated in DRC. In addition, Caveolin-1 (Cav-1), Fatty acid synthase (FASN) and Cytochrome P450 (CYP450) protein levels were elevated in DRC whereas in SCC, FASN and CYP450 levels were elevated. Downregulation of these molecules by respective siRNAs and/or by specific pharmacological inhibitors resensitized cells to paclitaxel. Interestingly, these drug resistant cells were also less sensitive to vinblastine, doxorubicin and methotrexate with the exception of cisplatin. Our results suggested that differential levels of P-gp, Cav-1 and FASN play a major role in acquired resistant phenotype whereas FASN level was associated with the presentation of inherent resistant phenotype in HCC.